2021
DOI: 10.1002/pon.5624
|View full text |Cite
|
Sign up to set email alerts
|

Burnout in oncology: Magnitude, risk factors and screening among professionals from Middle East and North Africa (BOMENA study)

Abstract: Background Burnout (BO) among oncology professionals (OP) is increasingly being recognized. Early recognition and intervention can positively affect the quality of care and patient safety. This study investigated the prevalence, work and lifestyle factors affecting BO among OPs in the Middle East and North Africa (MENA). Methods An online survey was conducted among MENA OPs between 10 February and 15 March 2020, using the validated Maslach Burnout Inventory of emotional exhaustion (EE), depersonalization (DP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…A total of 2015 hits were retrieved. After deleting duplicates (N = 386), irrelevant papers (N = 580), and exclusions (N = 915), we found 17 studies eligible to be included in this scoping review as shown in Figure 1 (3,15,(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46).…”
Section: Results Of the Database Searchmentioning
confidence: 99%
“…A total of 2015 hits were retrieved. After deleting duplicates (N = 386), irrelevant papers (N = 580), and exclusions (N = 915), we found 17 studies eligible to be included in this scoping review as shown in Figure 1 (3,15,(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46).…”
Section: Results Of the Database Searchmentioning
confidence: 99%
“…The odd of developing burnout was increased by 12-folds when the thought was “always” recurring. The recurring thought of quitting oncology was explored as a potential screening question in a previous study ( Abusanad et al, 2021 ). The desire of quitting can be explained either by career-choice regret that potentially resulted in burnout or it can be described as a consequence of burnout whereas causality cannot be ascertained.…”
Section: Discussionmentioning
confidence: 99%
“…A recent large study from the Middle East and North Africa (MENA) evaluated BO among oncologists of both genders showed that being an early-career physician, being from north African countries and having the thought of quitting oncology are associated with increased likelihood to report BO. Likewise, a high level of BO was reported among oncology professionals from different continents ( Abusanad et al, 2021 ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a study conducted in the United States [ 9 ] in 2017 showed a significant level of burnout among healthcare professionals with a prevalence increased over the years estimated at 45.6%. A systematic review of 182 studies from 45 countries showed a prevalence of burnout of up to 80.5% [ 10 ]. A recent survey conducted in 2020 among health professionals in the Middle East and North Africa (MENA) region showed a prevalence of burnout at 68% with significantly high scores of EE and DE (35% and 57%, respectively) with lower scores of professional accomplishments (49%) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%